Współpraca Kredyt Banku SA i Grupy Warta SA w ramach działalności bancassurance - oferta dla klientów indywidualnych - Owczarczyk, Beata (The cooperation of Kredyt Bank SA and Warta Group S.A. within bancassurance activity - a proposition for individual clients, 2007)
This article presents the kinds of the connections existing between Kredyt Bank S.A. and Warta S.A. within bancassurance. These two entities are running cooperation on the strength of non capital connections. The author of the article concentrates on showing kinds of products, which are offered by these institutions within cross-selling. There was also presented the meaning of bancassurance in everyday activity of these two entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 154-163